Achieving cultural heritage with multisensory virtual reality technologies - Miguel Melo (PsychTech & Health Journal)
Virtual Reality (VR) technologies aim at transporting their users to a virtual space. From the different fields of application, cultural heritage is a field with much to explore. A fact is that everyday pieces of cultural heritage are lost, whether due to natural phenomena that can destroy the natural landscapes or cultural traditions that are slowly and naturally disappears. What if we could leverage Virtual Reality to mitigate this issue?